Polymer Composition
Patent Information
- Application Number
- JP2023559782
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-04-15
- Filing Date
- 2022-04-07
- Publication Date
- 2025-04-01
AI Technical Summary
Fiber optic cable jackets face challenges in achieving low cyclic temperature shrinkback, high residual tensile elongation after heat aging, low unaged coefficient of friction, and laser printability, which are often conflicting properties in polymer compositions.
A polymer composition comprising polydimethylsiloxane with a weight average molecular weight of 550,000 g/mol to 650,000 g/mol, a polymeric UV stabilizer with a hindered amine moiety of 5,000 g/mol to 20,000 g/mol, and a high Mw comonomer content of 3.2% or more, along with specific ethylene-based polymers, to enhance elongation and reduce friction while maintaining laser printability.
The composition achieves cyclic temperature shrinkback of less than 2.5%, residual tensile elongation of 75% after heat aging, and unaged COF of 0.20, while being laser printable, thus meeting the demanding requirements of fiber optic cable jackets.
Abstract
Description
[Technical field]
[0001] The present disclosure relates generally to polymer compositions, and more particularly to polymer compositions exhibiting improved aging properties, reduced shrink-back, and at least one of a low unaged coefficient of friction and laser printability. [Background technology]
[0002] Introduction Fiber optic cables are useful for transmitting data at high speeds over long distances and are therefore seeing increased use. Fiber optic cables are trending towards smaller size and lighter weight, which requires new mini- and micro-cable technologies for fiber dense construction. Various performance characteristics are desired for polymer jackets when used in optical fibers. The first desired characteristic that polymer jacket materials exhibit is a cyclic temperature shrinkback of 2.5% or less to minimize signal attenuation. The second desired characteristic that polymer jackets exhibit is a residual tensile elongation at break of 75% or more after heat aging to ensure the life of the cable.
[0003] The desired properties of the polymer jacket are also dictated by the installation environment of the fiber optic cable. Fiber optic cables are often blown and / or pushed into existing conduits and ducts to increase fiber densification in the structure. In order for fiber optic cables to be effectively installed in this manner, the polymer composition of the jacket on the cable must have a low coefficient of friction ("COF"). The low coefficient of friction of the polymer composition ensures that the wires and cables do not resist sliding along the surface during installation. Typically, the polymer composition of the jacket must exhibit an unaged COF of 0.20 or less, as measured according to ASTM D1894, to be most effective in this application. Reduction of the COF of the polymer composition has been attempted using slip agents. Slip agents function as lubricants on the surface of the polymer composition during processing or in the use environment. These slip agents often function by migrating or blooming to the surface of the polymer composition, where they provide a coating that reduces the COF.
[0004] With improved fiber densification, there is an increasing need for easy and reliable cable identification. Laser beam printing is a method used for marking polymer compositions. Laser beam printing is useful because no physical contact between the printing ink or polymer composition and the printer is required, and laser printing allows fine marking on small cable designs and results in significantly higher print durability. However, not all polymer compositions are laser printable. For example, polymer compositions often require specific additives and compositions to make them laser printable. The requirements for making a polymer composition laser printable may conflict with the design of the polymer composition based on its end use. For example, a conventional jacket may contain carbon black at a concentration of about 2 weight percent to 3 weight percent to ensure 50% retention of elongation at break after 2000 hours of accelerated UV exposure. Unfortunately, conventional carbon black concentrations of about 2 weight percent or more result in poor contrast (i.e., 25% contrast or less) when laser printed.
[0005] Considering the complex balance of desirable properties, it would be surprising to discover a polymer composition useful as a cable jacket that exhibits cyclic temperature shrinkback of 2.5% or less, a residual tensile elongation at break of 75% after heat aging, which may also exhibit an unaged COF of 0.20, and / or which may be laser printable. Summary of the Invention
[0006] The present invention provides a polymer composition useful as a cable jacket that exhibits a cyclic temperature shrinkback of 2.5% or less, a residual tensile elongation at break of 75% after heat aging, may also exhibit an unaged COF of 0.20, and / or may be laser printable.
[0007] The present invention relates to a polymeric ultraviolet light stabilizer having a weight average molecular weight of 5,000 g / mol to 20,000 g / mol, and a polydimethylsiloxane having a weight average molecular weight of 550,000 g / mol to 650,000 g / mol, and a polymeric ultraviolet light stabilizer having a weight average molecular weight of 5,000 g / mol to 20,000 g / mol, and an "associated comonomer content" (defined below) of 0.6% by weight or more in combination with one or more of the following: a polydimethylsiloxane having a weight average molecular weight of 550,000 g / mol to 650,000 g / mol; and a polymeric ultraviolet light stabilizer having a weight average molecular weight of 5,000 g / mol to 20,000 g / mol, and a weight average molecular weight of 5,000 g / mol to 20,000 g / mol in combination with one or more of the following: 5 g / mol~10 5.5 The findings are the result of the discovery that polymer compositions using copolymers having a comonomer content of 3.2 wt.% or more over a range of weight average molecular weights (Mw) in g / mol ("high Mw comonomer content") can achieve the above-mentioned properties. Under tensile loading, the bond chains orient along the tensile axis during the final deformation stage. Strong bond chains are required for strain hardening to occur and to meet the requirement of 75% residual tensile elongation at break after heat aging. Without wishing to be bound by theory, it is believed that 10 5 g / mol~10 5.5It is believed that a high Mw comonomer content of 3.2 wt% or more over a molecular weight range of 1000 g / mol, in conjunction with a related comonomer content of 0.6 wt% or more, strengthens the tie molecules between the crystallites such that the elongation at break of the polymer composition is enhanced while maintaining the cyclic temperature shrinkback below 2.5%. Surprisingly, the introduction of one or more of a polydimethylsiloxane having a weight average molecular weight of 550,000 g / mol to 650,000 g / mol and a polymeric UV stabilizer having a weight average molecular weight of 5,000 g / mol to 20,000 g / mol containing a hindered amine moiety does not impair the polymer structure. It is believed that the molecular weight of the polydimethylsiloxane provides a viscosity similar to that of the copolymer, resulting in uniform dispersion within the polymer composition during melt compounding, and thus the polymer composition can exhibit an unaged COF of 0.20 or less when measured according to ASTM D1894. With respect to polymeric ultraviolet light stabilizers, it is believed that the higher molecular weight polymeric UV light stabilizers, in contrast to the oligomeric UV light stabilizers of the prior art, resist migration and separation during manufacture and use of the polymeric composition. The reduced migration of the polymeric UV light stabilizers provides the stabilizer with improved shelf life during extended exposure to UV light, thereby eliminating the need for carbon black and making the polymeric composition laser printable.
[0008] The present invention is particularly useful for wire and cable jackets.
[0009] According to a first aspect of the present disclosure, a polymer composition is a resin comprising an ethylene-based polymer and a copolymer of ethylene and an alpha-olefin comonomer, the resin having a molecular weight of 10 or more as measured by ethylene GPC. 5 g / mol~10 5.5and (ii) a polymeric UV stabilizer comprising a hindered amine moiety and having a weight average molecular weight of from 5,000 g / mol to 20,000 g / mol, as measured by component GPC.
[0010] According to a second aspect of the present disclosure, a polymer composition comprises both (i) and (ii).
[0011] According to a third aspect of the present disclosure, the polymer composition comprises 0.25 wt % to 2 wt % of a polymeric UV stabilizer, based on the total weight of the polymer composition.
[0012] According to a fourth aspect of the present disclosure, the polymer composition comprises 0.10 wt % to 0.25 wt % of carbon black, based on the total weight of the polymer composition.
[0013] According to a fifth feature of the present disclosure, the polymeric ultraviolet light stabilizer has a weight average molecular weight of 8,000 g / mol to 12,000 g / mol as measured according to component GPC, and the polymeric ultraviolet light stabilizer has Chemical Abstracts Service Registry Number 136504-96-6.
[0014] According to a sixth aspect of the present disclosure, the polymer composition comprises 35 wt% to 85 wt% of the copolymer, based on the total weight of the polymer composition.
[0015] According to a seventh feature of the present disclosure, the polymer composition comprises greater than 0 wt.% to 10 wt.% polydimethylsiloxane, based on the total weight of the polymer composition.
[0016] According to an eighth aspect of the present disclosure, the resin has a molecular weight of 105 g / mol~10 5.5 It has a high Mw comonomer content of 12.0 wt% or less over the molecular weight range in g / mol.
[0017] According to a ninth aspect of the present disclosure, not more than 30% by weight of the total weight of the resin is 10 5 g / mol~10 5.5 It has a molecular weight in the g / mol range.
[0018] According to a tenth feature of the present disclosure, a coated conductor includes a conductor and a polymer composition disposed at least partially about the conductor. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] As used herein, the term "and / or," when used with a list of two or more items, means that any one of the listed items can be used by itself, or any combination of two or more of the listed items can be used. For example, if a composition is described as containing components A, B, and / or C, the composition can contain A alone, B alone, C alone, A and B in combination, A and C in combination, B and C in combination, or A, B, and C in combination.
[0020] Unless otherwise stated, all ranges are inclusive of the endpoints.
[0021] Test methods refer to the most current test method as of the priority date of this document unless the test method number is dated with a two-digit number with a hyphen. References to test methods include both a reference to the testing society and the test method number. Test method organizations are referred to by one of the following abbreviations: ASTM refers to ASTM International (formerly known as the American Society for Testing and Materials), IEC refers to the International Electrotechnical Commission, EN refers to European Norm, DIN refers to Deutsches Institut fur Normung, and ISO refers to the International Organization for Standards.
[0022] As used herein, the term weight percent ("wt %"), unless otherwise specified, refers to the weight percentage that a component represents of the total weight of the polymer composition.
[0023] In this specification, the melt index (I 2 Melt index (I) values refer to values determined according to ASTM method D1238 at 190 degrees Celsius (°C) using a mass of 2.16 kilograms (Kilogram, kg) and are provided in units of grams dissolved per 10 minutes ("g / 10 min"). 21 ) values refer to values determined according to ASTM method D1238 at 190 degrees Celsius (°C) using a mass of 21.6 kg and are provided in units of grams dissolved per 10 minutes, g / 10 min.
[0024] Density values herein refer to values determined in accordance with ASTM D792 at 23° C. and are provided in units of grams per cubic centimeter ("g / cc").
[0025] As used herein, Chemical Abstract Services Registry Number ("CAS#") refers to the unique numerical identifier last assigned to a chemical compound by the Chemical Abstract Service as of the priority date of this document.
[0026] Polymer Composition The polymeric composition includes a resin and at least one of: (i) a polydimethylsiloxane having a weight average molecular weight of 550,000 g / mol to 650,000 g / mol as measured by ethylene GPC; and (ii) a polymeric UV stabilizer including a hindered amine moiety and having a weight average molecular weight of 5,000 g / mol to 20,000 g / mol as measured by component GPC. The resins include ethylene-based polymers and copolymers of ethylene and alpha-olefin comonomers ("copolymers"). The polymer compositions have a density of 0.945 g / cc to 0.970 g / cc in an unfilled state. For example, the unfilled density of the polymer compositions may be 0.945 g / cc or more, or 0.946 g / cc or more, or 0.948 g / cc or more, or 0.950 g / cc or more, or 0.952 g / cc or more, or 0.954 g / cc or more, or 0.955 g / cc or more, or 0.956 g / cc or more, or 0.958 g / cc or more, or 0.960 g / cc or more, or 0.962 g / cc or more, or 0.964 g / cc or more, or 0.966 g / cc or more, or 0.968 g / cc or more, while the same Sometimes, the viscosity may be 0.970 g / cc or less, or 0.968 g / cc or less, or 0.966 g / cc or less, or 0.964 g / cc or less, or 0.962 g / cc or less, or 0.960 g / cc or less, or 0.958 g / cc or less, or 0.956 g / cc or less, or 0.954 g / cc or less, or 0.952 g / cc or less, or 0.950 g / cc or less, or 0.948 g / cc or less, or 0.946 g / cc or less. As defined herein, the "unfilled state" of the polymer composition is defined as a polymer composition consisting essentially of a copolymer of ethylene and an alpha-olefin comonomer, an ethylene-based polymer, and at least one of a polydimethylsiloxane and a polymeric ultraviolet light stabilizer.
[0027] Copolymer One component of the polymer composition is a copolymer of ethylene and an alpha-olefin comonomer. "Polymer" means a polymeric compound that contains multiple monomers of the same or different types bonded together, and a copolymer is a polymer prepared from two or more different monomer types. Copolymers are polymers that are prepared from ethylene and one or more C olefins, such as propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, and 1-octene. 3 ~C 20 and an α-olefin comonomer. The copolymers can have a unimodal or multimodal molecular weight distribution. As used herein, "unimodal" refers to a polymeric material whose gel permeation chromatography curve has a molecular weight distribution ("MWD") that exhibits only a single peak and does not include a discernible second peak or even a shoulder or ridge relative to such single peak. In contrast, as used herein, "bimodal" refers to the presence of a two-component polymer when the MWD of the gel permeation chromatography curve can be indicated by having two peaks or by a ridge, shoulder, or tail of one component compared to the peak of the other component polymer. The copolymers can be prepared using Ziegler-Natta, chromium-based constrained geometry, or metallocene catalysts in slurry, gas-phase, or solution reactors.
[0028] The copolymers were characterized by Nuclear Magnetic Resonance (NMR) or Fourier-Transform Infrared (FIR). The polymeric olefin copolymer may comprise 50% or more, 60% or more, 70% or more, 80% or more, 85% or more, 90% or more, or 91% or more, or 92% or more, or 93% or more, or 94% or more, or 95% or more, or 96% or more, or 97% or more, or 97.5% or more, or 98% or more, or 99% or more, while at the same time 99.5% or less, or 99% or less, or 98% or less, or 97% or less, or 96% or less, or 95% or less, or 94% or less, or 93% or less, or 92% or less, or 91% or less, or 90% or less, or 85% or less, or 80% or less, or 70% or less, or 60% or less by weight ethylene, as measured using Fourier Transform Infrared (FTIR) spectroscopy.
[0029] The copolymer may be a high density polyethylene ("HDPE"), the copolymer having a density of 0.945 g / cc to 0.960 g / cc. For example, the density of the copolymer can be 0.945 g / cc or more, or 0.946 g / cc or more, or 0.948 g / cc or more, or 0.950 g / cc or more, or 0.952 g / cc or more, or 0.954 g / cc or more, or 0.955 g / cc or more, or 0.956 g / cc or more, or 0.958 g / cc or more, while simultaneously being 0.960 g / cc or less, or 0.958 g / cc or less, or 0.956 g / cc or less, or 0.955 g / cc or less, or 0.954 g / cc or less, or 0.952 g / cc or less, or 0.950 g / cc or less, or 0.948 g / cc or less, or 0.946 g / cc or less, as measured according to ASTM D792.
[0030] The copolymer may have a viscosity of 0.1 g / 10 min or more, or 0.3 g / 10 min or more, or 0.5 g / 10 min or more, or 1.0 g / 10 min or more, or 1.5 g / 10 min or more, or 2.0 g / 10 min or more, or 2.5 g / 10 min or more, or 3.0 g / 10 min or more, or 3.5 g / 10 min or more, or 4.0 g / 10 min or more, or 4.5 g / 10 min or more, or 5.0 g / 10 min or more, or 5.5 g / 10 min or more, or 6.0 g / 10 min or more, or 6.5 g / 10 min or more, or 7.0 g / 10 min or more, or 7.5 g / 10 min or more, or 8.0 g / 10 min or more, or 8.5 g / 10 min or more, or 9.0 g / 10 min or more, or 9.5 g / 10 min or more, while simultaneously , a melt index (I) of 10.0 g / 10 min or less, or 9.5 g / 10 min or less, or 9.0 g / 10 min or less, or 8.5 g / 10 min or less, or 8.0 g / 10 min or less, or 7.5 g / 10 min or less, or 7.0 g / 10 min or less, or 6.5 g / 10 min or less, or 6.0 g / 10 min or less, or 5.5 g / 10 min or less, or 5.0 g / 10 min or less, or 4.5 g / 10 min or less, or 4.0 g / 10 min or less, or 3.5 g / 10 min or less, or 3.0 g / 10 min or less, or 2.5 g / 10 min or less, or 2.0 g / 10 min or less, or 1.5 g / 10 min or less, or 1.0 g / 10 min or less, or 0.5 g / 10 min or less, or 0.3 g / 10 min or less 2 ).
[0031] The copolymer may have a viscosity of 90g / 10min or more, or 92g / 10min or more, or 94g / 10min or more, or 96g / 10min or more, or 98g / 10min or more, or 100g / 10min or more, or 102g / 10min or more, or 104g / 10min or more, or 106g / 10min or more, or 108g / 10min or more, or 110g / 10min or more, or 112g / 10min or more, or 114g / 10min or more, or 116g / 10min or more, or 118g / 10min, while simultaneously , a melt index ( 21 ).
[0032] The polymer composition may comprise 35% to 80% by weight of the copolymer. For example, the polymer composition may comprise 35% or more, or 40% or more, or 45% or more, or 50% or more, or 55% or more, or 60% or more, or 65% or more, or 70% or more, or 75% or more, or 80% or more by weight, while at the same time comprising 85% or less, or 80% or less, or 75% or less, or 70% or less, or 65% or less, or 60% or less, or 55% or less, or 50% or less, or 45% or less, or 40% or less by weight of the copolymer, based on the total weight of the polymer composition.
[0033] Ethylene-Based Polymers As noted above, the resin and polymer compositions may include an ethylene-based polymer. As used herein, an "ethylene-based" polymer is a polymer in which greater than 50% by weight of the monomers are ethylene, although other comonomers may be used. Ethylene-based polymers are polymers in which ethylene and one or more C olefins, such as propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, and 1-octene, are copolymers of ethylene and one or more C olefins, such as propylene, 1-butene, 1-pentene, 4-methyl-1-pentene, 1-hexene, and 1-octene. 3 ~C 20and an α-olefin comonomer. The ethylene-based polymer can have a monomodal or polymodal molecular weight distribution and can be used alone or in combination with one or more other types of ethylene-based polymers (e.g., a blend of two or more ethylene-based polymers differing in monomer composition and content, catalyst preparation, molecular weight, molecular weight distribution, density, etc.). When a blend of ethylene-based polymers is used, the polymers can be blended by any in-reactor or post-reactor process.
[0034] Ethylene-based polymers are characterized by Nuclear Magnetic Resonance (NMR) or Fourier-Transform Infrared (FIR). The polymeric olefin copolymer may comprise 50% or more, 60% or more, 70% or more, 80% or more, 85% or more, 90% or more, or 91% or more, or 92% or more, or 93% or more, or 94% or more, or 95% or more, or 96% or more, or 97% or more, or 97.5% or more, or 98% or more, or 99% or more, while at the same time 99.5% or less, or 99% or less, or 98% or less, or 97% or less, or 96% or less, or 95% or less, or 94% or less, or 93% or less, or 92% or less, or 91% or less, or 90% or less, or 85% or less, or 80% or less, or 70% or less, or 60% or less by weight ethylene, as measured using Fourier Transform Infrared (FTIR) spectroscopy. Other units of ethylene-based polymers include C propylene, 1-butene, 1-hexene, 4-methyl-1-pentene, and 1-octene. 3 , or C 4 , or C 6 , or C 8 , or C 10 , or C 12 , or C 16 , or C 18 , or C 20 Mention may be made of α-olefins.
[0035] The polymer composition can include 15% to 55% by weight of ethylene-based polymer. For example, the polymer composition includes 15% or more, or 20% or more, or 25% or more, or 30% or more, or 35% or more, or 40% or more, or 45% or more, or 50% or more by weight, while simultaneously including 55% or less, or 50% or less, or 45% or less, or 40% or less, or 35% or less, or 30% or less, or 25% or less, or 20% or less by weight of ethylene-based polymer.
[0036] The ethylene-based polymer may be a linear low density polyethylene ("LLDPE"). In the example of a LLDPE, the polymer composition may comprise 15% or more, or 16% or more, or 17% or more, or 18% or more, or 19% or more, or 20% or more, or 21% or more, or 22% or more, or 23% or more, or 24% or more, or 25% or more, or 26% or more, or 27% or more, or 28% or more, or 29% or more, while simultaneously comprising 30% or less, or 29% or less, or 28% or less, or 27% or less, or 26% or less, or 25% or less, or 24% or less, or 23% or less, or 22% or less, or 21% or less, or 20% or less, or 19% or less, or 18% or less, or 17% or less, or 16% or less by weight of ethylene-based polymer. Examples of LLDPE ethylene-based polymers can have a density, as measured by ASTM D792, of 0.910 g / cc or more, or 0.912 g / cc or more, or 0.914 g / cc or more, or 0.916 g / cc or more, or 0.918 g / cc or more, or 0.920 g / cc or more, or 0.922 g / cc or more, or 0.924 g / cc or more, or 0.926 g / cc or more, or 0.928 g / cc or more, while simultaneously being 0.930 g / cc or less, or 0.928 g / cc or less, or 0.926 g / cc or less, or 0.924 g / cc or less, or 0.922 g / cc or less, or 0.920 g / cc or less, or 0.918 g / cc or less, or 0.916 g / cc or less, or 0.914 g / cc or less, or 0.912 g / cc or less. Examples of LLPDEs for ethylene-based polymers have a melt index (I ) of 0.1 g / 10 min or more, or 0.2 g / 10 min or more, or 0.4 g / 10 min or more, or 0.56 g / 10 min or more, or 0.6 g / 10 min or more, or 0.8 g / 10 min or more, or 1.0 g / 10 min or more, or 1.2 g / 10 min or more, or 1.4 g / 10 min or more, while simultaneously being 1.5 g / 10 min or less, or 1.4 g / 10 min or less, or 1.2 g / 10 min or less, or 1.0 g / 10 min or less, or 0.8 g / 10 min or less, or 0.6 g / 10 min or less, or 0.56 g / 10 min or less, or 0.4 g / 10 min or less, or 0.2 g / 10 min or less. 2 ).
[0037] The ethylene-based polymer can be a plastomer. In the example of a plastomer, the polymer composition can include 15% by weight or more, or 16% by weight or more, or 17% by weight or more, or 18% by weight or more, or 19% by weight or more, while at the same time, 20% by weight or less, or 19% by weight or less, or 18% by weight or less, or 17% by weight or less, or 16% by weight or less of ethylene-based polymer. Exemplary ethylene-based polymer plastomers can have a density, as measured by ASTM D792, of 0.900 g / cc or more, or 0.901 g / cc or more, or 0.902 g / cc or more, or 0.903 g / cc or more, or 0.904 g / cc or more, or 0.905 g / cc or more, or 0.906 g / cc or more, or 0.907 g / cc or more, or 0.908 g / cc or more, or 0.909 g / cc or more, while simultaneously being 0.910 g / cc or less, or 0.909 g / cc or less, or 0.908 g / cc or less, or 0.907 g / cc or less, or 0.906 g / cc or less, or 0.905 g / cc or less, or 0.904 g / cc or less, or 0.903 g / cc or less, or 0.902 g / cc or less, or 0.901 g / cc or less. Examples of plastomers of ethylene-based polymers have a melt index (I) of 0.1 g / 10 min or more, or 0.2 g / 10 min or more, or 0.4 g / 10 min or more, or 0.6 g / 10 min or more, or 0.8 g / 10 min or more, or 0.86 g / 10 min or more, or 1.0 g / 10 min or more, or 1.2 g / 10 min or more, or 1.4 g / 10 min or more, while simultaneously being 1.5 g / 10 min or less, or 1.4 g / 10 min or less, or 1.2 g / 10 min or less, or 1.0 g / 10 min or less, or 0.8 g / 10 min or less, or 0.6 g / 10 min or less, or 0.56 g / 10 min or less, or 0.4 g / 10 min or less, or 0.2 g / 10 min or less. 2 ).
[0038] The ethylene-based polymer can be HDPE. In the example of HDPE, the polymer composition can include 45 wt% or more, or 46 wt% or more, or 47 wt% or more, or 48 wt% or more, or 49 wt% or more, or 50 wt% or more, or 51 wt% or more, or 52 wt% or more, or 53 wt% or more, or 54 wt% or more, while at the same time, 55 wt% or less, or 54 wt% or less, or 53 wt% or less, or 52 wt% or less, or 51 wt% or less, or 50 wt% or less, or 49 wt% or less, or 48 wt% or less, or 47 wt% or less, or 46 wt% or less of ethylene-based polymer. HDPE examples of ethylene-based polymers can have a density, as measured by ASTM D792, of 0.930 g / cc or more, or 0.932 g / cc or more, or 0.934 g / cc or more, or 0.936 g / cc or more, or 0.938 g / cc or more, or 0.940 g / cc or more, or 0.942 g / cc or more, or 0.944 g / cc or more, or 0.946 g / cc or more, or 0.948 g / cc or more, while simultaneously being 0.950 g / cc or less, or 0.948 g / cc or less, or 0.946 g / cc or less, or 0.944 g / cc or less, or 0.942 g / cc or less, or 0.940 g / cc or less, or 0.938 g / cc or less, or 0.936 g / cc or less, or 0.934 g / cc or less, or 0.932 g / cc or less. Examples of ethylene-based polymers, HDPE, have a melt index (I) of 0.1 g / 10 min or more, or 0.2 g / 10 min or more, or 0.4 g / 10 min or more, or 0.6 g / 10 min or more, or 0.8 g / 10 min or more, or 0.86 g / 10 min or more, or 1.0 g / 10 min or more, or 1.2 g / 10 min or more, or 1.4 g / 10 min or more, while simultaneously being 1.5 g / 10 min or less, or 1.4 g / 10 min or less, or 1.2 g / 10 min or less, or 1.0 g / 10 min or less, or 0.8 g / 10 min or less, or 0.6 g / 10 min or less, or 0.56 g / 10 min or less, or 0.4 g / 10 min or less, or 0.2 g / 10 min or less. 2 ).
[0039] The ethylene-based polymer can be an elastomer. In examples of elastomers, the polymer composition can include 10% by weight or more, or 11% by weight or more, or 12% by weight or more, or 13% by weight or more, or 14% by weight or more, while at the same time including 15% by weight or less, or 14% by weight or less, or 13% by weight or less, or 12% by weight or less, or 11% by weight or less of an ethylene-based polymer. Examples of elastomers of ethylene-based polymers are described in accordance with ASTM D792, the density may be 0.80 g / cc or more, or 0.81 g / cc or more, or 0.82 g / cc or more, or 0.83 g / cc or more, or 0.84 g / cc or more, or 0.85 g / cc or more, or 0.86 g / cc or more, or 0.87 g / cc or more, or 0.874 g / cc or more, or 0.88 g / cc or more, or 0.89 g / cc or more, while simultaneously being 0.90 g / cc or less, or 0.89 g / cc or less, or 0.88 g / cc or less, or 0.874 g / cc or less, or 0.87 g / cc or less, or 0.86 g / cc or less, or 0.85 g / cc or less, or 0.84 g / cc or less, or 0.83 g / cc or less, or 0.82 g / cc or less, or 0.81 g / cc or less. Examples of elastomers of ethylene-based polymers have a melt index (I) of 0.1 g / 10 min or more, or 0.2 g / 10 min or more, or 0.4 g / 10 min or more, or 0.6 g / 10 min or more, or 0.8 g / 10 min or more, or 0.86 g / 10 min or more, or 1.0 g / 10 min or more, or 1.2 g / 10 min or more, or 1.4 g / 10 min or more, while simultaneously being 1.5 g / 10 min or less, or 1.4 g / 10 min or less, or 1.2 g / 10 min or less, or 1.0 g / 10 min or less, or 0.8 g / 10 min or less, or 0.6 g / 10 min or less, or 0.56 g / 10 min or less, or 0.4 g / 10 min or less, or 0.2 g / 10 min or less. 2 ).
[0040] It will be understood that more than one of the examples of ethylene-based polymers LLDPE, plastomer, HDPE, and elastomer may be utilized in the polymer composition without departing from the teachings provided herein.
[0041] Polyethylene glycol The polymer composition may include polyethylene glycol, which refers to an oligomer or polymer of ethylene oxide represented by structural formula (I): H-(O-CH 2 -CH 2 ) q -OH Structural formula (I) In the formula, q refers to the number of repeat units in the polyethylene glycol polymer. The q value of the polyethylene glycol can range from 200 to 10,000.
[0042] The weight average molecular weight of the polyethylene glycol, as measured by component GPC, is 10,000 g / mol or more, or 20,000 g / mol or more, or 30,000 g / mol or more, or 35,000 g / mol or more, or 40,000 g / mol or more, or 45,000 g / mol or more, or 50,000 g / mol or more, or 55,000 g / mol or more, or 60,000 g / mol or more, or 65,000 g / mol or more, or 70,000 g / mol or more, or 75,000 g / mol or more, or 80,000 g / mol or more, or 85,000 g / mol or more, or 90,000 g / mol or more, or 95,000 g / mol 100,000 g / mol or less, or 90,000 g / mol or less, or 85,000 g / mol or less, or 80,000 g / mol or less, or 75,000 g / mol or less, or 70,000 g / mol or less, or 65,000 g / mol or less, or 60,000 g / mol or less, or 55,000 g / mol or less, or 50,000 g / mol or less, or 45,000 g / mol or less, or 40,000 g / mol or less, or 35,000 g / mol or less, or 30,000 g / mol or less, or 25,000 g / mol or less, or 20,000 g / mol or less, or 15,000 g / mol or less. Blends of different average molecular weight polyethylene glycols of the same or different weight percents may be utilized in the polymer composition.
[0043] The polyethylene glycol may be 0.1% to 2% by weight of the polymer composition. The polymer composition may contain 0.1% or more by weight of polyethylene glycol, or 0.2% or more by weight, or 0.3% or more by weight, or 0.4% or more by weight, or 0.5% or more by weight, or 0.6% or more by weight, or 0.7% or more by weight, or 0.8% or more by weight, or 0.9% or more by weight, or 1.0% or more by weight, or 1.1% or more by weight, or 1.2% or more by weight, or 1.3% or more by weight, or 1.4% or more by weight, or 1.5% or more by weight, or 1.6% or more by weight, or 1.7% or more by weight, or 1.8% or more by weight, or 1.9% or more by weight. % or more, while at the same time comprising 2.0% or less, or 1.9% or less, or 1.8% or less, or 1.7% or less, or 1.6% or less, or 1.5% or less, or 1.4% or less, or 1.3% or less, or 1.2% or less, or 1.1% or less, or 1.0% or less, or 0.9% or less, or 0.8% or less, or 0.7% or less, or 0.6% or less, or 0.5% or less, or 0.4% or less, or 0.3% or less, or 0.2% or less.
[0044] Polydimethylsiloxane The polymer composition may include polydimethylsiloxane ("polydimethylsiloxane, PDMS"). The PDMS may be unsubstituted or substituted. A "substituted PDMS" is a PDMS in which at least one methyl group of the PDMS is substituted with a substituent. Non-limiting examples of the substituent include halogen atoms (such as chlorine, fluorine, bromine, and iodine), halogen atom-containing groups (such as chloromethyl, perfluorobutyl, trifluoroethyl, and nonafluorohexyl), oxygen atom-containing groups (such as hydroxyl, alkoxy groups (such as methoxy and ethoxy), (meth)acryl epoxy, and carboxyl), nitrogen atom-containing groups (such as amino, amide, and cyano functional groups), sulfur atom-containing groups (such as mercapto), hydrogen, C 2 ~C 10 Alkyl group (e.g. ethyl group), C 2 ~C 10Examples of suitable substituted PDMS include alkynyl groups, alkenyl groups (such as vinyl and hexenyl groups), aryl groups (such as phenyl and substituted phenyl groups), cycloalkyl groups (such as cyclohexane groups), and combinations thereof. The substituted methyl groups may be terminal or non-terminal methyl groups. Non-limiting examples of suitable substituted PDMS include those in which at least one alkyl is C 2 ~C 10 Examples of such PDMS include alkyl, trialkylsilyl, dialkylhydroxysilyl, dialkylhydrogensilyl, dialkylalkenylsilyl, dialkylvinylsilyl, dimethylhydroxysilyl, and dimethylvinylsilyl terminated PDMS.
[0045] The PDMS has a weight average molecular weight of 550,000 g / mol to 650,000 g / mol, as measured according to component GPC, which is described in more detail below. For example, the PDMS has a weight average molecular weight of 550,000 g / mol or more, or 560,000 g / mol or more, or 570,000 g / mol or more, or 580,000 g / mol or more, or 590,000 g / mol or more, or 600,000 g / mol or more, or 610,000 g / mol or more, or 620,000 g / mol or more, or 630,000 g / mol or more, or 640,000 g / mol or more, as measured according to component GPC. / mol or more, while at the same time having a Mw of 650,000 g / mol or less, or 640,000 g / mol or less, or 630,000 g / mol or less, or 620,000 g / mol or less, or 610,000 g / mol or less, or 600,000 g / mol or less, or 590,000 g / mol or less, or 580,000 g / mol or less, or 570,000 g / mol or less, or 560,000 g / mol or less. The polymer composition may be free of polydimethylsiloxanes having a weight average molecular weight of 30,000 g / mol to 300,000 g / mol as measured according to component GPC. As used herein, the term "free of" is defined to mean that the polymer composition contains 0.01% by weight or less of the material that it is said to be free of.
[0046] The polymeric composition may comprise 0.1 wt% or more, or 0.5 wt% or more, or 1 wt% or more, or 2 wt% or more, or 3 wt% or more, or 4 wt% or more, or 5 wt% or more, or 6 wt% or more, or 7 wt% or more, or 8 wt% or more, or 9 wt% or more, while simultaneously 10 wt% or less, or 9 wt% or less, or 8 wt% or less, or 7 wt% or less, or 6 wt% or less, or 5 wt% or less, or 4 wt% or less, or 3 wt% or less, or 2 wt% or less, or 1 wt% or less of PDMS, based on the total weight of the polymeric composition.
[0047] Second polydimethylsiloxane The polymer composition may include a second polydimethylsiloxane having a lower Mw than the PDMS having a Mw of 550,000 g / mol to 650,000 g / mol. The second PDMS may be substituted or unsubstituted and may be terminated with any of the above.
[0048] The second PDMS has a weight average molecular weight of 2,000 g / mol to 15,000 g / mol, as measured by component GPC. For example, the PDMS has a weight average molecular weight of 2,000 g / mol or more, or 3,000 g / mol or more, or 4,000 g / mol or more, or 5,000 g / mol or more, or 6,000 g / mol or more, or 7,000 g / mol or more, or 8,000 g / mol or more, or 9,000 g / mol or more, or 10,000 g / mol or more, or 11,000 g / mol or more, or 12,000 g / mol or more, or 13,000 g / mol or more, or 14,000 g / mol or more, as measured by component GPC. / mol or more, while simultaneously having a Mw of 15,000 g / mol or less, or 14,000 g / mol or less, or 13,000 g / mol or less, or 12,000 g / mol or less, or 11,000 g / mol or less, or 10,000 g / mol or less, or 9,000 g / mol or less, or 8,000 g / mol or less, or 7,000 g / mol or less, or 6,000 g / mol or less, or 5,000 g / mol or less, or 4,000 g / mol or less, or 3,000 g / mol or less.
[0049] The polymeric composition may comprise 0.1 wt% or more, or 0.5 wt% or more, or 1 wt% or more, or 2 wt% or more, or 3 wt% or more, or 4 wt% or more, or 5 wt% or more, or 6 wt% or more, or 7 wt% or more, or 8 wt% or more, or 9 wt% or more, while simultaneously 10 wt% or less, or 9 wt% or less, or 8 wt% or less, or 7 wt% or less, or 6 wt% or less, or 5 wt% or less, or 4 wt% or less, or 3 wt% or less, or 2 wt% or less, or 1 wt% or less of PDMS, based on the total weight of the polymeric composition.
[0050] Carbon Black The polymer composition may include carbon black. Carbon black has the CAS Registry Number 1333-86-4. Carbon black is useful for preventing damage to the polymer composition due to exposure to sunlight, but may adversely affect the laser printability of the polymer composition. The polymer composition may include carbon black in an amount of 0.00 wt% to 0.25 wt% based on the total weight of the polymer composition in laser printable examples. For example, the polymer composition may have a molecular weight of 0.00% or more, 0.05% or more, or 0.06% or more, or 0.07% or more, or 0.08% or more, or 0.09% or more, or 0.10% or more, or 0.11% or more, or 0.12% or more, or 0.13% or more, or 0.14% or more, or 0.15% or more, or 0.16% or more, or 0.17% or more, or 0.18% or more, or 0.19% or more, or 0.20% or more, or 0.21% or more, or 0.22% or more, or 0.23% or more, or 0.24% or more, based on the total weight of the polymer composition. At the same time, it may contain 0.25% by weight or less, or 0.24% by weight or less, or 0.23% by weight or less, or 0.22% by weight or less, or 0.21% by weight or less, or 0.20% by weight or less, or 0.19% by weight or less, or 0.18% by weight or less, or 0.17% by weight or less, or 0.16% by weight or less, or 0.15% by weight or less, or 0.14% by weight or less, or 0.13% by weight or less, or 0.12% by weight or less, or 0.11% by weight or less, or 0.10% by weight or less, or 0.09% by weight or less, or 0.08% by weight or less, or 0.07% by weight or less, or 0.06% by weight or less, 0.05% by weight or less, or 0.01% by weight or less of carbon black. In non-laser printable examples, the polymer composition may comprise 1 wt. % or more, or 2 wt. % or more, or 3 wt. % or more, or 4 wt. % or more, or 5 wt. % or more of carbon black, based on the total weight of the polymer composition.
[0051] The carbon black may have an average particle size of about 10 nm to about 300 nm, or 10 nm to 100 nm, or 15 nm to 50 nm, as measured using laser diffraction spectroscopy. The carbon black may be added to the polymer composition as a neat or pure component, or may be added as part of a masterbatch in combination with one or more other components.
[0052] Polymeric UV Stabilizers The polymer composition may include a polymeric ultraviolet stabilizer. The polymeric stabilizer includes one or more hindered amine moieties. As used herein, a hindered amine moiety is an amine moiety that is present on an aromatic ring such that the lone pair of the nitrogen atom is conjugated to the aromatic ring. An example of a polymeric stabilizer that includes a hindered amine moiety has CAS Registry Number 136504-96-6 and is described as a polymer of 1,3-propanediamine, N1,N1'-1,2-ethanediylbis-, 2,4,6-trichloro-1,3,5-triazine, and N-butyl-2,2,6,6-tetramethyl-4-piperidinamine. A commercially available example of a polymeric stabilizer is sold under the trade name UVASORB™ HA10 by 3V Sigma USA (Georgetown, South Carolina, USA). The polymeric stabilizer has a weight average molecular weight of 5,000 grams / mole ("g / mol") to 20,000 g / mol, as measured by component GPC. For example, the polymeric stabilizer may have a weight average molecular weight of 5,000 g / mol or more, or 6,000 g / mol or more, or 7,000 g / mol or more, or 8,000 g / mol or more, or 9,000 g / mol or more, or 10,000 g / mol or more, or 11,000 g / mol or more, or 12,000 g / mol or more, or 13,000 g / mol or more, or 14,000 g / mol or more, or 15,000 g / mol or more, or 16,000 g / mol or more, or 17,000 g / mol or more, or 18,000 g / mol or more, or 19,000 g / mol. 1,000 g / mol or less, while simultaneously having a weight average molecular weight of 20,000 g / mol or less, or 19,000 g / mol or less, or 18,000 g / mol or less, or 17,000 g / mol or less, or 16,000 g / mol or less, or 15,000 g / mol or less, or 14,000 g / mol or less, or 13,000 g / mol or less, or 12,000 g / mol or less, or 11,000 g / mol or less, or 10,000 g / mol or less, or 9,000 g / mol or less, or 8,000 g / mol or less, or 7,000 g / mol or less, or 6,000 g / mol or less.
[0053] The polymer composition may include a polymeric stabilizer in an amount of 0.25% to 2.00% by weight based on the total weight of the polymer composition. For example, the polymer composition may include 0.25% by weight or more, or 0.50% by weight or more, or 0.75% by weight or more, or 1.00% by weight or more, or 1.25% by weight or more, or 1.50% by weight or more, or 1.75% by weight or more, while at the same time, 2.00% by weight or less, or 1.75% by weight or less, or 1.50% by weight or less, or 1.25% by weight or less, or 1.00% by weight or less, or 0.75% by weight or less, or 0.50% by weight or less of the polymeric stabilizer based on the total weight of the polymer composition.
[0054] Oligomeric UV Stabilizers The polymer composition may include an oligomeric UV stabilizer. The oligomeric stabilizer may include one or more hindered amine moieties. An example of an oligomeric stabilizer has CAS Registry Number 136504-96-6 and is described as a polymer of 1,3-propanediamine, N1,N1'-1,2-ethanediylbis-, 2,4,6-trichloro-1,3,5-triazine, and N-butyl-2,2,6,6-tetramethyl-4-piperidinamine. Such an oligomeric stabilizer is sold under the trade name UVASORB™ HA88 by 3V Sigma USA (Georgetown, South Carolina, USA). Another example of an oligomeric stabilizer has the CAS Registry Number 71878-19-8 and is described as poly[[6-[(1,1,3,3-tetramethylbutyl)amino]-1,3,5-triazine-2,4-diyl][(2,2,6,6-tetramethyl-4-piperidinyl)imino]-1,6-hexanediyl[(2,2,6,6-tetramethyl-4-piperidinyl)imino]]. Such an oligomeric stabilizer is sold under the trade name CHIMASSORB™ 944 LD by BASF (Ludwigshafen, Germany).
[0055] The oligomeric stabilizer has a weight average molecular weight of 1,000 g / mol to 5,000 g / mol when measured according to component GPC.For example, the oligomeric stabilizer can have a weight average molecular weight of 1,000 g / mol or more, or 1,500 g / mol or more, or 2,000 g / mol or more, or 2,500 g / mol or more, or 3,000 g / mol or more, or 3,500 g / mol or more, or 4,000 g / mol or more, or 4,500 g / mol or more, while at the same time being 5,000 g / mol or less, or 4,500 g / mol or less, or 4,000 g / mol or less, or 3,500 g / mol or less, or 3,000 g / mol or less, or 2,500 g / mol or less, or 2,000 g / mol or less, or 1,500 g / mol or less when measured according to component GPC.
[0056] The polymer composition may include the oligomeric stabilizer in an amount of 0.25 wt% to 2.00 wt%, based on the total weight of the polymer composition. For example, the polymer composition may include 0.25 wt% or more, or 0.50 wt% or more, or 0.75 wt% or more, or 1.00 wt% or more, or 1.25 wt% or more, or 1.50 wt% or more, or 1.75 wt% or more, while simultaneously including 2.00 wt% or less, or 1.75 wt% or less, or 1.50 wt% or less, or 1.25 wt% or less, or 1.00 wt% or less, or 0.75 wt% or less, or 0.50 wt% or less of the oligomeric stabilizer, based on the total weight of the polymer composition.
[0057] resin As mentioned above, both the copolymer of the resin and the ethylene-based polymer each contain a comonomer. By adjusting the weight percent of the comonomer and at what molecular weight fraction of the resin the comonomer is present, the polymer composition can meet or exceed the cyclic temperature shrink back and tensile elongation at break mechanical properties described above. The portion of the resin in which the comonomer content is to be adjusted is about 10 5 g / mol~10 5.5 The proportion of resins with a weight average molecular weight of g / mol. 5 g / mol~10 5.5The percentage of resin having a weight average molecular weight in g / mol is defined herein as the "high Mw weight fraction," as described in more detail below in the GPC test method.
[0058] The polymer composition may comprise a high Mw weight fraction that is 0.02 or more, or 0.04 or more, or 0.06 or more, or 0.08 or more, or 0.10 or more, or 0.12 or more, or 0.14 or more, or 0.16 or more, or 0.18 or more, or 0.20 or more, or 0.22 or more, or 0.24 or more, or 0.26 or more, or 0.28 or more, while simultaneously being 0.30 or less, or 0.28 or less, or 0.26 or less, or 0.24 or less, or 0.22 or less, or 0.20 or less, or 0.18 or less, or 0.16 or less, or 0.14 or less, or 0.12 or less, or 0.10 or less, or 0.08 or less, or 0.06 or less, or 0.04 or less, or 0.02 or less. The weight percent of the high Mw weight fraction of the combined copolymer and ethylene-based polymer is calculated by multiplying the weight fraction value by 100.
[0059] The average comonomer content of the high Mw weight fraction ("high Mw comonomer content") is determined from short chain branching data obtained via ethylene GPC as described below in the Ethylene GPC Test Methods. The polymer composition may comprise a high Mw comonomer content of 3.2 wt% or more, or 3.4 wt% or more, or 3.6 wt% or more, or 3.8 wt% or more, or 4.0 wt% or more, or 4.2 wt% or more, or 4.4 wt% or more, or 4.6 wt% or more, or 4.8 wt% or more, or 5.0 wt% or more, or 5.2 wt% or more, or 5.4 wt% or more, or 5.6 wt% or more, or 5.8 wt% or more, while simultaneously being 6.0 wt% or less, or 5.8 wt% or less, or 5.6 wt% or less, or 5.4 wt% or less, or 5.2 wt% or less, or 5.0 wt% or less, or 4.8 wt% or less, or 4.6 wt% or less, or 4.4 wt% or less, or 4.2 wt% or less, or 4.0 wt% or less, or 3.8 wt% or less, or 3.6 wt% or less, or 3.4 wt% or less.
[0060] The product of the high Mw weight fraction and the high Mw comonomer content is defined as the "relevant comonomer content" and thus represents the weight percent of the total mass of comonomer present in all chains of total size Log10 of Mw between 5.00 and 5.50 compared to the total mass of the polymer composition. The polymer composition may comprise a relevant comonomer content of 0.6 wt% or more, or 0.8 wt% or more, or 1.0 wt% or more, or 1.2 wt% or more, or 1.4 wt% or more, or 1.6 wt% or more, or 1.8 wt% or more, or 2.0 wt% or more, or 2.2 wt% or more, or 2.4 wt% or more, or 2.6 wt% or more, or 2.8 wt% or more, or 3.0 wt% or more, or 3.2 wt% or more. In other words, the polymer composition may comprise a relevant comonomer content of 10 wt% or more, as measured by ethylene GPC. 5 g / mol~10 5.5 The total comonomer contained within the moiety having a molecular weight in the g / mol range is at least 0.6 wt. % of the total weight of the polymer composition.
[0061] Mechanical properties The polymeric composition may exhibit a residual tensile elongation at break after aging of greater than 75%, as described in more detail below. For example, the residual elongation at break of the polymeric composition may be 76% or more, or 80% or more, or 85% or more, or 90% or more, or 95% or more, while at the same time being 100% or less, or 95% or less, or 90% or less, or 85% or less, or 80% or less.
[0062] The polymeric composition may exhibit a cyclic temperature shrinkback of less than 2.50%, as described in more detail below. For example, the cyclic temperature shrinkback of the polymeric composition is 2.45% or less, or 2.40% or less, or 2.35% or less, or 2.30% or less, or 2.25% or less, or 2.20% or less, or 2.15% or less, or 2.10% or less, or 2.05% or less, or 2.00% or less, or 1.95% or less, or 1.90% or less, or 1.85% or less, or 1.80% or less, or 1.75% or less, or 1.70% or less, or 1.65% or less, or 1.60% or less, or It may be 1.55% or less, while at the same time being 1.50% or more, or 1.55% or more, or 1.60% or more, or 1.65% or more, or 1.70% or more, or 1.75% or more, or 1.80% or more, or 1.85% or more, or 1.90% or more, or 1.95% or more, or 2.00% or more, or 2.05% or more, or 2.10% or more, or 2.15% or more, or 2.20% or more, or 2.25% or more, or 2.30% or more, or 2.35% or more, or 2.40% or more.
[0063] The polymeric composition exhibits both an unaged COF and an aged COF. As used herein, the unaged COF is the COF exhibited by a polymeric composition without any intentional aging or delay in testing after its manufacture. As used herein, the aged COF is the COF exhibited by a polymeric composition after being held at a temperature of 55° C. for 336 hours (i.e., 2 weeks) without any intentional delay or aging prior to heating.
[0064] The unaged COF of the polymer composition, as measured according to ASTM D1894, can be 0.01 or more, or 0.02 or more, or 0.04 or more, or 0.06 or more, or 0.08 or more, or 0.10 or more, or 0.12 or more, or 0.14 or more, or 0.16 or more, or 0.18 or more, while simultaneously being 0.20 or less, or 0.18 or less, or 0.16 or less, or 0.14 or less, or 0.12 or less, or 0.10 or less, or 0.08 or less, or 0.06 or less, or 0.04 or less, or 0.02 or less.
[0065] The aging COF of the polymer composition, as measured according to ASTM D1894, can be 0.01 or more, or 0.02 or more, or 0.04 or more, or 0.06 or more, or 0.08 or more, or 0.10 or more, or 0.12 or more, or 0.14 or more, or 0.16 or more, or 0.18 or more, while simultaneously being 0.20 or less, or 0.18 or less, or 0.16 or less, or 0.14 or less, or 0.12 or less, or 0.10 or less, or 0.08 or less, or 0.06 or less, or 0.04 or less, or 0.02 or less.
[0066] Additives The polymeric composition may include additional additives in the form of antioxidants, processing aids, coupling agents, antistatic agents, additional nucleating agents, slip agents, lubricants, viscosity modifiers, tackifiers, antiblocking agents, surfactants, extender oils, acid scavengers, flame retardants, and metal deactivators. The polymeric composition may include 0.01% to 5% by weight of one or more of the additional additives. The additives may be added individually as neat components, combined, and / or added in one or more masterbatches.
[0067] The polymer composition may include one or more particulate fillers, such as various mineral-based fillers, including glass fibers or nanocomposites. Fillers, especially those containing elongated or platelet-like particles that provide a higher aspect ratio (length / thickness), may improve modulus and post-extrusion shrinkage properties. The fillers may have a median size or d50 of less than 20 μm, less than 10 μm, or less than 5 μm. The fillers may be surface treated to facilitate wetting or dispersion in the polymer composition. Specific examples of suitable fillers include, but are not limited to, calcium carbonate, silica, quartz, fused quartz, talc, mica, clay, kaolin, wollastonite, feldspar, aluminum hydroxide, and graphite. The fillers may be included in the polymer composition in an amount ranging from 2 to 30% by weight, or from 5 to 30% by weight, based on the total weight of the polymer composition.
[0068] Processing aids may include metal salts of fluoroplastics such as polytetrafluoroethylene or fluorinated ethylene propylene, carboxylic acids such as zinc stearate or calcium stearate; fatty acids such as stearic acid, oleic acid, or erucic acid; fatty amides such as stearamide, oleamide, erucamide, or N,N'-ethylenebis-stearamide; polyethylene waxes; oxidized polyethylene waxes; polymers of ethylene oxide; copolymers of ethylene oxide and propylene oxide; vegetable waxes; petroleum waxes; non-ionic surfactants; silicone fluids and polysiloxanes.
[0069] Antioxidants include hindered phenols such as tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydro-cinnamate)]methane; bis[(beta-(3,5-di-tert-butyl-4-hydroxybenzyl)methylcarboxyethyl)]-sulfide, 4,4'-thiobis(2-methyl-6-tert-butylphenol), 4,4'-thiobis(2-tert-butyl-5-methylphenol), 2,2'-thiobis(4-methyl-6-tert-butylphenol), and thiodiethylenebis(3,5-di-tert-butyl-4-hydroxy)-hydrocinnamate; tris(2,4-di-tert-butylphenyl)phosphatase. phosphites and phosphonites such as sphite and di-tert-butylphenyl-phosphonite; thio compounds such as dilauryl thiodipropionate, dimyristyl thiodipropionate, and distearyl thiodipropionate; various siloxanes; polymeric 2,2,4-trimethyl-1,2-dihydroquinoline, n,n'-bis(1,4-dimethylpentyl-p-phenylenediamine), alkylated diphenylamines, 4,4'-bis(alpha,alpha-dimethylbenzyl)diphenylamine, diphenyl-p-phenylenediamine, mixed di-aryl-p-phenylenediamines, and other hindered amine antidegradants or stabilizers.
[0070] Compounding and Formation of Coated Conductors The components of the polymer composition may be added to a batch or continuous mixer for melt blending to form a melt blended composition. The components may be added in any order or by first preparing one or more masterbatches to blend with the other components. The melt blending may be performed at a temperature above the melting point of the highest melting polymer. The melt blended composition may then be delivered to an extruder or injection molding machine or passed through a die to be molded into the desired article, or converted into pellets, tapes, strips, or films, or other forms for storage or preparation of the material to be fed to the next molding or processing step. Optionally, if molded into pellets or some similar configuration, the pellets or the like may be coated with an anti-blocking agent to facilitate handling during storage.
[0071] Examples of compounding equipment used include internal batch mixers such as BANBURY™ or BOLLING™ internal mixers. Alternatively, continuous single or twin screw mixers such as FARRELL™ continuous mixers, WERNER™ and PFLEIDERER™ twin screw mixers, or BUSS™ kneading continuous extruders can be used. The type of mixer utilized and the operating conditions of the mixer affect the properties of the composition such as viscosity, volume resistivity, and extrusion surface smoothness.
[0072] A coated conductor may be formed from the polymer composition. The coated conductor includes a conductor and a coating. The coating includes the polymer composition. The polymer composition is at least partially disposed around the conductor to produce the coated conductor. The conductor may include a conductive metal or an optically transparent structure.
[0073] The process for making coated conductors includes mixing the polymer compositions and heating in an extruder to at least the melting temperature of the polymer components to form a polymer melt blend, and then coating the polymer melt blend onto the conductor. The term "on" includes direct or indirect contact between the polymer melt blend and the conductor. The polymer melt blend is in an extrudable state.
[0074] The polymer composition is disposed on and / or around the conductor to form a coating. The coating may be one or more inner layers, such as an insulating layer. The coating may entirely or partially cover or otherwise surround or encase the conductor. The coating may be the only component surrounding the conductor. Alternatively, the coating may be one layer of a multi-layer jacket or sheath that encases the conductor. The coating may be in direct contact with the conductor. The coating may be in direct contact with an insulating layer that surrounds the conductor. EXAMPLES
[0075] material The following materials are used in the following examples:
[0076] The copolymer has a density of 0.955 g / cc and a melt index (I 2 ), and a melt index (I 21 ) and is available from The Dow Chemical Company (Midland, MI).
[0077] EP1 has a density of 0.920 g / cc and a melt index (I 2 ), and a melt index (I 21 ) is a UNIPOL™ gas-phase unimodal ethylene-butene polymer.
[0078] Si Gum is a blend of 35 weight percent polydimethylsiloxane that is dimethylvinylsiloxy terminated and has a Mw of 696,000 g / mol as measured by component GPC, with the remainder being medium density polyethylene with a density of 0.935 g / cc and a melt flow rate of 0.65 g per 10 minutes at 190° C. Silicone rubber PDMS is available from the Dow Chemical Company (Midland, MI).
[0079] CBMB is a carbon black masterbatch containing 45% by weight carbon black and is available from The Dow Chemical Company (Midland, MI).
[0080] HA10 is a polymeric ultraviolet light stabilizer having CAS Registry Number 136504-96-6 and a weight average molecular weight of about 10,000 as measured according to component GPC. HA10 is commercially available from 3V Sigma USA (Georgetown, South Carolina, USA) under the trade name UVASORB™ HA10.
[0081] HA88 is an oligomeric UV stabilizer having CAS Registry Number 136504-96-6 and a weight average molecular weight, as measured by component GPC, of about 3,000. HA88 is commercially available from 3V Sigma USA (Georgetown, South Carolina, USA) under the trade name UVASORB™ HA88.
[0082] PEG is a polyethylene glycol with a weight average molecular weight of 20,000 g / mol and is available from Clariant (Germany).
[0083] AO1 is a sterically hindered phenolic antioxidant with the chemical name pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) and is commercially available as IRGANOX 1010™ from BASF (Ludwigshafen, Germany).
[0084] AO2 is a hydrolytically stable phosphite treatment stabilizer having the chemical name tris(2,4-ditert-butylphenyl)phosphite and is commercially available as IRGAFOS® 168 from BASF (Ludwigshafen, Germany).
[0085] PA is a fluoroplastic processing aid commercially available under the trade name DYNAMAR™ FX 5912, available from 3M, Saint Paul, Minnesota, USA.
[0086] Sample preparation Inventive Examples ("IE") 1-3 and Comparative Example ("CE") 1 were compounded in a Mini BANBURY (1.2 kg) or BANBURY (12 kg) batch mixer from HF Mixing Group. Drop temperature was 150° C. After compounding, the samples were extruded and pelletized.
[0087] The pelletized samples were formed into plaques and jackets for different mechanical tests. Plaques were prepared by compression molding the pellets on an arbor press preheated at 180°C. The pellets were placed into molds of different thicknesses as per the test requirements. The samples were heated to 180°C for 4 minutes and then pressed at 3.45 megapascals (MPa) for 3 minutes followed by 17.24 MPa for 3 minutes. The samples were cooled in the press at 15°C / min to 23°C and then removed. Jacket samples were prepared by extruding the polymer composition onto the conductor at 180°C-240°C using a 6.35 cm wire extrusion line from Davis-Standard at 91 meters per minute with a wall thickness of 0.05 cm.
[0088] Heat aging of the samples for tensile elongation at break was performed by preheating a Type I oven (per ASTM D5423) to 100° C. The samples were then placed in the preheated oven and aged for 10 days. After aging, the samples were then conditioned at 23° C. and 50% relative humidity for 24 hours.
[0089] Compression molded plaques (1.27 mm x 101.6 mm x 101.6 mm) of the test samples were prepared and laser marked according to the parameters in Table 1.
[0090] [Table 1]
[0091] Test Method Triple detector gel permeation chromatography ("Ethylene GPC") was performed using a chromatography system consisting of a PolymerChar GPC-IR (Valencia, Spain) high temperature GPC chromatograph equipped with an internal IR5 infrared detector (IR5) and a 4-capillary viscometer (DV) coupled to an Agilent Technologies 2-angle laser light scattering (LS) detector model 2040. For all light scattering measurements, a 15 degree angle is used for measurement purposes. The autosampler oven compartment was set at 160°C and the column compartment was set at 150°C. The columns used were four Agilent "Mixed A" 30 cm, 20 micrometer linear mixed bed columns. The chromatography solvent used was 1,2,4-trichlorobenzene containing 200 ppm butylated hydroxytoluene (BHT). The solvent source was nitrogen sparged. The injection volume employed was 200 μL and the flow rate was 1.0 mL / min.
[0092] Calibration and calculations were performed for conventional molecular weight moments and distributions following methods similar to conventional GPC procedures (using a 20um "Mixed A" column).
[0093] A systematic approach to determining multiple detector offsets was performed in a manner consistent with that published by Balke, Mourey, et. al. (Mourey and Balke, Chromatography Polym. Chpt 12, (1992)) (Balke, Thitiratsakul, Lew, Cheung, Mourey, Chromatography Polym. Chpt 13, (1992)) using PolymerChar GPCOne™ software to optimize triple detector log (MW and IV) results from broad homopolymer polyethylene standards (Mw / Mn>3) to narrow standard column calibration results from narrow standard calibration curves. As used herein, "MW" refers to molecular weight.
[0094] Absolute molecular weight data were obtained using PolymerChar GPCOne™ software in a manner consistent with that published by Zimm (Zimm, BH, J. Chem. Phys., 16, 1099 (1948)) and Kratochvil (Kratochvil, P., Classical Light Scattering from Polymer Solutions, Elsevier, Oxford, NY (1987)). The total injected concentration used in determining the molecular weight was obtained from the mass detector area and mass detector constant derived from a suitable linear polyethylene homopolymer or one of the polyethylene standards of known weight average molecular weight. The calculated molecular weight (using GPCOne™) was obtained using the light scattering constant and refractive index concentration coefficient, dn / dc, of 0.104, derived from one or more of the polyethylene standards described below. In general, the mass detector response (IR5) and light scattering constant (determined using GPCOne™) should be determined from a linear standard with a molecular weight greater than about 50,000 g / mol. Viscometer calibration (determined using GPCOne™) can be accomplished using the method described by the manufacturer, or alternatively, by using published values of a suitable linear standard, such as Standard Reference Material (SRM) 1475a (available from the National Institute of Standards and Technology (NIST)). The viscometer constant (obtained using GPCOne™) is calculated by relating the specific viscosity area (DV) and injected mass for the calibration standard to its intrinsic viscosity (IV). The chromatographic concentration is assumed to be low enough to preclude addressing the second viral coefficient effect.
[0095] The absolute weight average molecular weight (Mw(Abs)) is obtained by dividing the area integrated chromatogram of the light scattering (LS) (factored by the light scattering constant) (using GPCOne™) by the mass constant and the mass recovered from the mass detector (IR5) area. The molecular weight and intrinsic viscosity responses are extrapolated (using GPCOne™) at the chromatographic end where the signal to noise is low. The other respective moments, Mn (Abs) and Mz (Abs) is calculated according to the following formulas 1 and 2.
[0096]
number
[0097] Conventional GPC: The chromatography system consisted of a PolymerChar GPC-IR (Valencia, Spain) high temperature GPC chromatograph equipped with an internal IR5 infrared detector (IR5) coupled to a Precision Detectors (now Agilent Technologies) 2-angle laser light scattering (LS) detector model 2040. For all light scattering measurements, a 15 degree angle is used for measurement purposes. The autosampler oven compartment was set at 160°C and the column compartment was set at 150°C. The columns used were four Agilent "Mixed A" 30 cm, 20 micrometer linear mixed bed columns. The chromatographic solvent used was 1,2,4-trichlorobenzene containing 200 ppm butylated hydroxytoluene (BHT). The solvent source was nitrogen sparged. The injection volume employed was 200 μL and the flow rate was 1.0 mL / min.
[0098] Calibration of the GPC column set was performed with 21 narrow molecular weight distribution polystyrene standards with molecular weights ranging from 580 g / mol to 8,400,000 g / mol, prepared in six "cocktail" mixtures with at least 10-fold separation between individual molecular weights. Standards were purchased from Agilent Technologies. Polystyrene standards were prepared at 0.025 grams in 50 milliliters of solvent for molecular weights equal to or greater than 1,000,000 g / mol, and 0.05 grams in 50 milliliters of solvent for molecular weights less than 1,000,000 g / mol. The polystyrene standards were dissolved at 80° C. for 30 minutes with gentle agitation. The peak molecular weights of the polystyrene standards were converted to polyethylene molecular weights using Equation 1 (as described in Williams and Ward, J. Polym. Sci., Polym. Let., 6, 621 (1968)).
[0099]
number
[0100] A fifth-order polynomial was used to fit each of the polyethylene-equivalent calibration points, with a small adjustment to A (approximately 0.395 to 0.440) to correct for column resolution and band broadening effects for a linear homopolymer polyethylene standard obtained at 120,000 g / mol (Mw).
[0101] Total plate counts for the GPC column set were performed using decane (prepared at 0.04 g in 50 milliliters of TCB). Plate counts (Equation 4) and symmetry (Equation 5) were measured with a 200 microliter injection according to the following equations:
[0102]
number
[0103]
number
[0104] Samples were prepared semi-automatically using the PolymerChar "Instrument Control" software to target sample weights of 2 mg / ml and add the solvent (containing 200 ppm BHT) via the PolymerChar high temperature autosampler to septa-capped vials that had been pre-sparged with nitrogen. Samples were dissolved at 160° C. for 2 hours under "slow" shaking.
[0105] Calculations of Mn(conv), Mw(conv), and Mz(conv) were performed based on GPC results using the internal IR5 detector (measurement channel) of a PolymerChar GPC-IR chromatograph, according to Equations 6-8, using PolymerChar GPCOne™ software, using baseline-subtracted IR chromatograms at equally spaced data collection points (i), and polyethylene equivalent molecular weights obtained from a narrow standard calibration curve at point (i) from Equation 1.
[0106]
number
[0107] To monitor deviations over time, a flow rate marker (decane) was introduced into each sample via a micropump controlled by a PolymerChar GPC-IR system. This flow rate marker (FM) was used to linearly correct the pump flow rate (flow rate (apparent)) of each sample by RV matching the respective decane peak in the sample (RV (FM sample)) with that of the decane peak in the narrow standard calibration (RV (FM calibrated)). Any change in time of the decane marker peak is then assumed to be related to a linear shift in flow rate (flow rate (effective)) throughout the run. To facilitate the highest accuracy of the RV measurement of the flow rate marker peak, a least squares fitting routine is used to fit the peaks of the flow rate marker concentration chromatogram to a quadratic equation. The first derivative of the quadratic equation is then used to solve for the true peak position. After calibrating the system based on the flow rate marker peak, the effective flow rate (relative to the narrow standard calibration) is calculated as follows: Equation 9. Processing of the flow rate marker peaks was performed via PolymerChar GPCOne™ software. The allowable flow correction is such that the effective flow is within ±2% of the apparent flow. Flow (effective) = Flow (nominal) * (RV(FM calibrated) / RV(FM sample)) (Equation 9)
[0108] The IR5 detector ratio calibration was performed using known short chain branching (SCB) frequencies (SCB) ranging from homopolymer (0 SCB / 1000 total C) to approximately 40 SCB / 1000 total C (where total C = carbons in the backbone + carbons in the branches). 13 A series of measurements was performed using at least ten ethylene-based polymer standards (polyethylene homopolymers and ethylene / octene copolymers) with molecular weights of 100,000 and 100,000 g / mol, as determined by the GPC-LALS processing method described above. Each standard had a weight average molecular weight between 36,000 g / mol and 126,000 g / mol, as determined by the GPC-LALS processing method described above. Each standard had a molecular weight distribution (Mw / Mn) between 2.0 and 2.5, as determined by the GPC-LALS processing method described above.
[0109] The "IR5 area ratio (or "IR5 area ratio") of the "IR5 methyl channel sensor baseline subtracted area response" to the "IR5 measurement channel sensor baseline subtracted area response" メチルチャネル領域 / IR5 測定チャネル領域 ")" (Standard filters and filter wheel supplied by PolymerChar: Part Number IR5_FWM01 were included as part of the GPC-IR instrument) were calculated for each of the "SCB" standards. A linear fit of the SCB frequency versus "IR5 Area Ratio" was constructed in the form of Equation 10. SCB / total number of carbon atoms 1000=A 0 +[A 1 ×(IR5 メチルチャネル領域 / IR5 測定チャネル領域 )] (Equation 10)
[0110] In Equation 10, A 0 is the intercept of "SCB / total carbon number 1000" at the "IR5 region ratio" of zero, and A 1 is the slope of "SCB / 1000 total carbons" versus "IR5 region ratio" and represents the increase in SCB / 1000 total carbons as a function of "IR5 region ratio".
[0111] A series of "linear baseline-subtracted chromatographic heights" for the chromatograms generated by the "IR5 methyl channel sensor" were established as a function of column elution volume to generate a baseline-corrected chromatogram (methyl channel). A series of "linear baseline-subtracted chromatographic heights" for the chromatograms generated by the "IR5 measurement channel" were established as a function of column elution volume to generate a baseline-corrected chromatogram (measurement channel).
[0112] The "IR5 height ratio" of the "baseline corrected chromatogram (methyl channel)" to the "baseline corrected chromatogram (measurement channel)" was calculated for each column elution volume index (each equally spaced index representing one data point per second at 1 mL / min elution) across the sample integration boundary. The "IR5 height ratio" was multiplied by a factor A 1 Multiply by coefficient A 0was added to this result to generate the predicted SCB frequency for the sample. The result was converted to mole percent comonomer as per Equation 11 below.
[0113]
number
[0114] In Equation 11, "SCB f " has "SCB / total carbon number of 1000" and "comonomer length" = 8.
[0115] The mole % comonomer is then converted to weight % comonomer by using the molecular weights of octene and ethylene.
[0116] By the above method, the weight percent comonomer can be calculated for a sample or any portion of a sample. Use of this technique in combination with conventional GPC analysis allows the weight percent comonomer to be determined as a function of molecular weight (C8 i ).
[0117] The high Mw weight fraction is determined from the conventional GPC method described above. The high Mw weight fraction is the total mass fraction measured to have a Log10 of Mw of at least 5.00 and less than 5.50 based on conventional GPC, as shown in Equation 12.
[0118]
number
[0119] The high Mw comonomer content was calculated by using the weighted average comonomer weight % reported over these molecular weight ranges, as shown in Equation 13.
[0120]
number
[0121] The product of the high Mw weight fraction and the high Mw comonomer content is the weight fraction of the resin that consists of comonomer contained within a polymer chain of a particular molecular weight. This product is the relevant comonomer.
[0122] The weight average molecular weights of polydimethylsiloxane, polymeric light stabilizer, oligomeric light stabilizer, and polyethylene glycol are measured by "component GPC" according to the following parameters. The component GPC is performed using a Viscotek™ GPC Max using triple detection capability. The Viscotek™ TDA305 unit is equipped with a differential refractometer, an online differential pressure viscometer, and low angle light scattering (LALS: detection angles of 7° and 90°). The mobile phase is toluene HPLC grade for PDMS. The mobile phase may be different for the measurement of polymeric light stabilizer, oligomeric light stabilizer, and polyethylene glycol. The columns are two Varian PL Gel Mixed C columns (7.5×300 mm, 5 μm particle size) and one Varian PL Gel Guard column (7.5×300 mm) with 5 fractom injection volume, 1 mL / min flow rate, and 37 min run time. The column and detector temperatures are 40° C. The software used is Omnisec 4.6.1 (Viscotek™). The detector is calibrated by injecting a narrow polystyrene standard (Mw 68, 100 g / mol) of known concentration. It will be understood that the PDMS, polymeric light stabilizers, oligomeric light stabilizers, and polyethylene glycols may have their molecular weights reported by the supplier of the material, and such reported molecular weights may be utilized in lieu of component GPC measurements.
[0123] The elongation at break was measured at 25 mm / min using an extensometer according to IEC 60811-501 on dog bone excised from the plaque specimens.
[0124] Density was measured at 23° C. according to ASTM D792.
[0125] The melt index was measured in accordance with ASTM D1238 at 190°C with a load of 2.16 kg (I 2 ) or 21.6 kg load (I 21 ) were used for the measurements.
[0126] Cyclic temperature shrink-back testing was performed on the jacket specimens. Cyclic temperature shrink-back was performed by conditioning the jacket specimens in an oven from 40°C to 100°C at a ramp rate of 0.5°C / min. The specimens were held at 100°C for 60 minutes and then the temperature was returned to 40°C at a rate of 0.5°C / min. The jackets were held at 40°C for 20 minutes and then the temperature cycle was repeated four more times for a total of five cycles. Shrinkage is reported as the percent change in jacket length from pre-test to post-test and was measured using a ruler accurate to 1.6mm for 61cm long specimens.
[0127] The gray contrast ratio was calculated using ImageJ software (NIH) for markings produced with a beam wavelength of 1064.6 nm, frequency of 60 kHz, intensity of 90%, and marking speed of 2000 mm / s.
[0128] result Table 1 provides compositional data for IE1-IE3 and CE1. Table 2 provides mechanical testing results for IE1-IE3 and CE1. Tensile elongation at break is provided for both unaged ("Unaged TE") and heat aged samples ("Aged TE"). The residual elongation at break after aging ("Residual TE") is calculated by dividing the aged TE value by the TE value of the sample.
[0129] [Table 2]
[0130] [Table 3]
[0131] Referring now to Tables 1 and 2, CE1 can meet the desired residual tensile elongation values, but cannot achieve an unaged COF of 0.20 or less. CE1 is not laser printable based on the amount of carbon black required to ensure weatherability. IE1-IE3 can exhibit cyclic temperature shrinkback of 2.5% or less, can exhibit residual tensile elongation at break of 75% or more after heat aging, and can exhibit one or both of an unaged COF of 0.20 or less and a gray contrast of 25% or more. As can be seen, the addition of polydimethylsiloxane having a weight average molecular weight of 550,000 g / mol to 650,000 g / mol in IE2 and IE3 can produce samples with dramatically reduced unaged and aged coefficients of friction while maintaining a cyclic temperature shrinkback of 2.5% or less and a tensile elongation at break of 75% or more after heat aging. IE1 and IE3 demonstrate that by removing the carbon black and replacing it with a polymeric UV stabilizer containing hindered amine moieties and having a weight average molecular weight of 5,000 g / mol to 20,000 g / mol, samples can be produced that are laser printable (i.e., have a gray contrast of 25% or greater) while maintaining a cyclic temperature shrink back of 2.5% or less after heat aging and a tensile elongation at break of 75% or greater. IE3 demonstrates that samples meeting all of the above physical properties can be produced when the polymer composition comprises both a polydimethylsiloxane containing a copolymer, having an associated comonomer content of 0.6% by weight or greater, and having a weight average molecular weight of 550,000 g / mol to 650,000 g / mol, and a polymeric UV stabilizer containing hindered amine moieties and having a weight average molecular weight of 5,000 g / mol to 20,000 g / mol.
Claims
1. 1. A polymer composition comprising:
1. A resin comprising an ethylene-based polymer and a copolymer of ethylene and an alpha-olefin comonomer, the resin having a molecular weight of 10 or less as measured by ethylene gel permeation chromatography (GPC). 5 g / mol to 10 5.5 a resin having a high Mw comonomer content of 3.2 wt% or greater based on the total weight of said resin over a weight average molecular weight range in g / mol, said polymer composition having a related comonomer content of 0.6 wt% or greater; 1. A polymer composition comprising: (i) a polydimethylsiloxane having a weight average molecular weight of 550,000 g / mol to 650,000 g / mol, as measured by component GPC; and (ii) a polymeric UV stabilizer comprising a hindered amine moiety and having a weight average molecular weight of 5,000 g / mol to 20,000 g / mol, as measured by component GPC.
2. The polymer composition of claim 1 , wherein the polymer composition comprises both (i) and (ii).
3. The polymer composition of claim 1 or 2, wherein the polymer composition comprises from 0.25% to 2% by weight of the polymeric UV stabilizer, based on the total weight of the polymer composition.
4. 4. The polymer composition of claim 3, comprising 0.10 wt.% to 0.25 wt.% of carbon black, based on the total weight of the polymer composition.
5. 4. The polymer composition of claim 3, wherein the polymeric UV stabilizer has a weight average molecular weight of 8,000 g / mol to 12,000 g / mol as measured according to component GPC, and the polymeric UV stabilizer has Chemical Abstracts Service Registry Number 136504-96-6.
6. The polymer composition of claim 1 or 2, wherein the polymer composition comprises 35% to 85% by weight of the copolymer, based on the total weight of the polymer composition.
7. The polymer composition of claim 1 or 2, wherein the polymer composition comprises from 0 wt% to 10 wt% of the polydimethylsiloxane, based on the total weight of the polymer composition.
8. The resin has a molecular weight of 10 5 g / mol to 10 5.5 3. The polymer composition of claim 1 or 2 having a high Mw comonomer content of up to 12.0 wt% over the molecular weight range in g / mol.
9. 30% or less by weight of the total weight of the resin is 10% or less by weight as measured by ethylene GPC. 5 g / mol to 10 5.5 9. The polymer composition of claim 8 having a molecular weight in the range of g / mol.
10. A coated conductor comprising: A conductor; and the polymer composition of claim 1 or 2 disposed at least partially around the conductor.